1996
DOI: 10.1021/ja954332t
|View full text |Cite
|
Sign up to set email alerts
|

Multichromophoric Cyclodextrins. 4. Light Conversion by Antenna Effect

Abstract: A water soluble β-cyclodextrin (CD-NA) bearing seven naphthoyl chromophores forms very stable 1:1 complexes with a merocyanine laser dye DCM-OH (4-(dicyanomethylene)-2-methyl-6-(p-(bis(hydroxyethyl)amino)styryl)-4H-pyran). The antenna effect, i.e. energy transfer from the naphthoyl antenna chromomophores to the encased dye, is shown to occur with 100% efficiency. The stability of the complexes is very high (K s ≈ 105) owing to the contribution of the naphthoate residues. The structural features of the complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
78
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 30 publications
4
78
0
Order By: Relevance
“…Inclusion of an energy acceptor in the cavity leads to a supramolecular complex in which the antenna effect, that is energy transfer from the appended antenna chromophores to the encased acceptor, can be thoroughly studied. [4,6] The circular arrangement of the antenna chromophores is reminiscent of the antenna system of photosynthetic bacteria [11] which further emphasizes the interest of multichromophoric cyclodextrins. Another outstanding feature is the capability of antennainduced photoreactions within the cavity; specific effects are indeed expected from selective excitation of the reactants included in the cavity through energy transfer from the appended chromophores.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inclusion of an energy acceptor in the cavity leads to a supramolecular complex in which the antenna effect, that is energy transfer from the appended antenna chromophores to the encased acceptor, can be thoroughly studied. [4,6] The circular arrangement of the antenna chromophores is reminiscent of the antenna system of photosynthetic bacteria [11] which further emphasizes the interest of multichromophoric cyclodextrins. Another outstanding feature is the capability of antennainduced photoreactions within the cavity; specific effects are indeed expected from selective excitation of the reactants included in the cavity through energy transfer from the appended chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…[9] In our previous work devoted to the antenna effect in an inclusion complex of a water-soluble b-cyclodextrin CD-NA with a merocyanine (DCMOH) (Figure 1) we observed an excimer emission from the appended chromophores. [6] Later on, investigation of the complexation of several cationic surfactants [9] suggested that the excimer formation in CD-NA is likely to result from a head-to-tail interaction between two naphthalene units located on opposite sides of the functionalized primary rim. For a thorough study of the antenna effect, excimer formation should be avoided because excimers act as energy traps in the excitation energy hopping process, and energy transfer to an acceptor included in the cavity can occur from both monomer and excimer forms of the antenna chromophores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the enormous research interest in such host-guest systems over the last decade, a great variety of possible guests and cyclodextrin derivatives has been studied for a number of applications. 6,7 Derivatives of 7-amino-4-methylcoumarins are widely known as highly efficient laser dyes. However, an interest in obtaining water soluble complexes of cyclodxtrins with laser dyes, to improve their spectral luminescent and generating characteristics for subsequent phototechnological application, has appeared only recently.…”
mentioning
confidence: 99%
“…8 Until now such systems were mainly studied by fluorescent techniques. [7][8][9] This paper deals with the formation of complexes of cyclodextrins ( -and γ-CD) with 7-amino-4-methylcoumarin (COU120) and 7-N,N-diethylamino-4-methylcoumarin (COU1), and investigation of the capabilities of PDMS in the study of such complex formation.…”
mentioning
confidence: 99%